Evaluation on the perception of final year dental students on their confidence level regarding endodontic treatments: a cross sectional analysis - Ali Al-Kadhim, Aws Hashim; Nor Azan, Awathif; Muhammad Salim, Muaz; Yousif Al-Ani, Sarah Taha; Jaafar, Azlan (IIUM Journal of Orofacial and Health Sciences, 2022)
Endodontics procedures are difficult and complicated that most of the practitioners would encounter. Therefore, dental students should gain their confidence and competent during their training. This research aimed to study the perception of final year students on confidence level regarding endodontic treatments from all public universities and their opinions on the quality of endodontic education. A Google Form was used to disseminate an online questionnaire to all dental students from public universities across Malaysia. The survey included both scaled answer and open-ended questions. 184 responses out of 235 students, were obtained (response rate = 78%). Perception of competence and confidence were significantly greater amongst the students from research-based universities group (P < 0.05). 93.5% (n=179) of participants agree that they were confident to do endodontic procedure on anterior tooth, whilst on posterior tooth, only 75.5% (n=139) were confident. Only 6.5 percent of participants (n = 12) did not feel confident doing root canal treatment on single-rooted teeth, but 76.1 percent (n = 140) did not feel competent performing root canal treatment on multirooted teeth. Over 90% of the students rated the quality and the amount of time spent on endodontic education were adequate at their respective university as ?5 on a Likert scale (1 = inadequate to 10 = adequate). In addition, when they were asked to give the suggestion on how to improve the quality of endodontic education, 10.9% of the students suggested to increase the number of practical session and to do regular discussion regarding endodontic cases. It is vital to improve undergraduate endodontic education in order to raise students' perceptions of their confidence and competence when doing root canal therapy.